Renewable biocomposites based on cellulose fibers and dimer fatty acid polyamide: Experiments and modeling of the stress–strain behavior. Issue 1 (15th July 2016) - Boumbimba, R. Matadi; Wang, K.; Hablot, E.; Bahlouli, N.; Ahzi, S.; Avérous, L.
Abstract : Dimer fatty acid‐based polyamide (DAPA) was reinforced with cellulose fibers (CF) from 5 to 15 wt%. The mechanical behaviors in terms of dynamic responses were examined by dynamic mechanical analysis and split Hopkinson pressure bars at various temperatures and strain rates. Both DAPA matrix and DAPAC biocomposites showed fiber concentration, temperatures, and strain rates sensibilities. A constitutive elasto‐viscoplastic model was developed to predict the finite deformation response for these materials. In this, to account for strain rate, temperature and cellulose concentration effects in elastic behavior, a new formulation of statistical model of Richeton was proposed. A modified cooperative model, based on the recognition of the effective activation energy and volume, was used for the prediction of the composites yield stress. Eight‐chain model was also used to capture the large stretch hyperelastic behavior for both DAPA and DAPAC. The constitutive model predictions were found to be in good agreement with the experimental data. POLYM. ENG. SCI., 57:95–104, 2017. © 2016 Society of Plastics Engineers